Research on the influence of aero-optical effects on starlight atmospheric refraction navigation under supersonic conditions - Yang, Yufeng; Song, Ningning (Frontiers in Applied Mathematics and Statistics, 2022)
In the starlight atmospheric refraction navigation when the starlight transmits in the supersonic flow field, the aero-optical effect will reduce the accuracy of navigation. In this paper, the aircraft model is established by ICEM and Fluent is used to simulate the atmosphere density distribution at different altitudes and speeds. Then, the principle of geometric optics is used to track the starlight, the angular deviation of starlight transmission is deduced, and finally, the influence of different speeds and altitudes on starlight atmospheric refraction navigation is analyzed. The results show that the aero-optical effect produced by supersonic vehicles is related to the flight altitude and flight speed. Taking the flight altitude of 20km and 30km as an example, when the flight speed is Mach 2, the angular deviation caused by the aero-optical effect is 1.045" and 0.699" respectively, and when the flight speed is Mach 10, the angular deviation is 20.075" and 4.643" respectively. Therefore, the aero-optical effect can be ignored at the altitude of 30km and above. However, the influence of the aero-optical effect at 20km needs to be judged according to the flight speed.